Fixation patterns during recognition of personally familiar and unfamiliar faces - Van Belle, Goedele; Ramon, Meike; Lefèvre, Philippe; Rossion, Bruno (Frontiers in Psychology, 2010)
Previous studies recording eye movements have rendered inconclusive findings with respect to processing differences between familiar and unfamiliar faces. We argue that this can be attributed to a number of factors that differ across studies: the type and extent of familiarity with stimuli presented, the varying spatial resolution of visual information and/or specifics, the definition of areas of interest subject to analyses, as well as the fact that the time course of scan patterns is often neglected. Here we sought to address these issues by recording gaze patterns in a face recognition task with personally familiar and unfamiliar faces, without predefining areas of interest and investigating potential processing differences at each individual fixation. We found that after a first fixation on the center of mass of the face—suggesting an initial holistic perception—and a subsequent left eye bias, local features were focused and explored more for familiar than unfamiliar faces. Although the number of fixations made did not differ for un-/familiar faces, the locations of fixations began to differ much earlier than when the familiarity decisions were provided. This suggests that without strict time constraints, different types of information are collected relatively early on familiar and unfamiliar faces.